2007
DOI: 10.1093/njaf/24.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Do Improvement Harvests Mitigate Oak Decline in Missouri Ozark Forests?

Abstract: Since the 1970s, oak decline has been a chronic problem throughout the oak-dominated forests of the Missouri Ozarks. Prior research indicates that environmental stress, particularly drought, leads to the onset of oak decline. Consequently, some scientists and managers have advocated thinning and intermediate harvesting to maintain or improve tree vigor and growth, thereby leaving stands less susceptible to pathogens and pests that are frequently the ultimate cause of mortality of declining trees. However, few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…Similarly, in Idaho, thinning was related to an increase in the number of new lethal infections per tree of Pinus monticola (western white pine) by C. ribicola 5 years after treatment (Hungerford et al, 1982). In an experiment in a forest in Missouri, USA, where a range of oak species are subject to "oak decline" that may be caused by a range of root pathogens or insects, thinning in the form of "improvement harvests" (selective cutting to remove trees that were declining and to reduce tree density) did not significantly alter the incidence of oak decline after 10 (Meadows et al, 2013) or 14 years (Dwyer et al, 2007;Meadows et al, 2013).…”
Section: Thinningmentioning
confidence: 99%
“…Similarly, in Idaho, thinning was related to an increase in the number of new lethal infections per tree of Pinus monticola (western white pine) by C. ribicola 5 years after treatment (Hungerford et al, 1982). In an experiment in a forest in Missouri, USA, where a range of oak species are subject to "oak decline" that may be caused by a range of root pathogens or insects, thinning in the form of "improvement harvests" (selective cutting to remove trees that were declining and to reduce tree density) did not significantly alter the incidence of oak decline after 10 (Meadows et al, 2013) or 14 years (Dwyer et al, 2007;Meadows et al, 2013).…”
Section: Thinningmentioning
confidence: 99%
“…Restoring fire through prescribed burning in high-hazard stands will also reduce stem density in the mid-storey and understorey, especially by controlling tolerant species competing with oak advance growth. In addition to long-term management strategies, salvage and sanitation cutting applied after the onset of oak decline may even be helpful for mitigating the effects of decline on the remaining red oaks (Dwyer et al, 2007).…”
Section: Conclusion and Management Recommendationsmentioning
confidence: 99%
“…Forest harvesting has been widely advocated to reduce or prevent exposure to predisposing factors in oak decline by removing susceptible species and declining trees [14]–[16]. Prior research has examined the effects of forest harvesting on managing oak decline at stand scales over relatively short-time frames (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…less than 20 years). Three widely used harvest alternatives for reducing vulnerability to oak decline are: clearcutting, group selection, and thinning [14], [16]. Burrill et al [17] showed that thinning conducted in even-aged stands before reaching rotation age was useful in preventing future oak decline by increasing stand vigor and controlling species composition.…”
Section: Introductionmentioning
confidence: 99%